STRATEGI IMPLEMENTASI SISTEM EKONOMI ISLAM DALAM MENGHADAPI MASYARAKAT EKONOMI ASEAN (MEA) - Salman Munthe (Jurnal Perspektif Ekonomi Darussalam (Darussalam Journal of Economic Perspec, 2015)
Asean Economic Community (AEC) in 2015 was the realization of a free market in Southeast Asia that has been done gradually began ASEAN Summiting in Singapore in 1992. The purpose of the establishment of the ASEAN Economic Community (AEC)is to enhance economic stability in the ASEAN region, and expected to address the problem- problems in the economic field between ASEAN countries. MEA consequences of the agreement in the form of free flow of goods to the ASEAN countries, the impact of the free flow of services, the impact of the free flow of investment, the impact of the flow of skilled labor, and the impact of the free flow of capital. These things can certainly result in positive or negative for the Indonesian economy. Therefore, from the government side also run the strategies and measures that Indonesia is ready and able to take advantage of MEA MOMENTUM.Masyarakat Ekonomi Asean (MEA) 2015 merupakan realisasi pasar bebas di Asia Tenggara yang telah dilakukan secara bertahap mulai KTT ASEAN di Singapura pada tahun 1992. Tujuan dibentuknya Masyarakat Ekonomi ASEAN (MEA) untuk meningkatkan stabilitas perekonomian di kawasan ASEAN, serta diharapkan mampu mengatasi masalah-masalah di bidang ekonomi antar negara ASEAN. Konsekuensi atas kesepakatan MEA tersebut berupa aliran bebas barang bagi negara-negara ASEAN, dampak arus bebas jasa, dampak arus bebas investasi, dampak arus tenaga kerja terampil, dan dampak arus bebas modal. Hal-hal tersebut tentunya dapat berakibat positif atau negative bagi perekonomian Indonesia. Oleh karena itu dari sisi pemerintah juga dilakukan strategi dan langkah-langkah agar Indonesia siap dan dapat memanfaatkan momentum MEA.